Early administration of abciximab reduces mortality in female patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention (from the EUROTRANSFER Registry) - Dziewierz, Artur (Springer US, 2012)
The present study assessed the impact of early administration of abciximab in female and male patients with ST-segment elevation myocardial infarction (STEMI) transferred for primary angioplasty (PPCI). Data were gathered for 1,650 consecutive patients with STEMI transferred for PPCI from hospital networks in seven countries in Europe from November 2005 to January 2007 (the EUROTRANSFER Registry population). Among 1,086 patients who received abciximab, there were 186 women and 541 men who received abciximab early (>30 min before PPCI), and 86 women and 273 men treated with late abciximab. Female patients were high-risk individuals, with advanced age and increased rate of ischemic events. Early abciximab administration was associated with enhanced patency of the infarct-related artery before PPCI, and improved epicardial flow after PPCI in both women and men. Early abciximab in women led to the decrease in ischemic events, including 30 day (adjusted OR 0.26, 95 % CI 0.10–0.69, p = 0.007) and 1 year (adjusted OR 0.37, 95 % CI 0.16–0.84, p = 0.017) mortality reduction. In contrast, the reduction in 30 day (adjusted OR 0.69, 95 % CI 0.35–1.39, p = 0.27) and 1 year (adjusted OR 0.68, 95 % CI 0.38–1.22, p = 0.19) mortality was not significant in men. The frequency of bleeding events was similar in the early abciximab group compared to the late abciximab group in both women and men. Early administration of abciximab improved patency of the infarct-related artery before and after PPCI, and led to improved survival in female patients with STEMI.